Strain engineering on electronic structure and carrier mobility in monolayer GeP3. (18th May 2018) - Zeng, Bowen; Long, Mengqiu; Zhang, Xiaojiao; Dong, Yulan; Li, Mingjun; Yi, Yougen; Duan, Haiming
Abstract: Using density functional theory coupled with the Boltzmann transport equation with relaxation time approximation, we have studied the strain effect on the electronic structure and carrier mobility of two-dimensional monolayer GeP3 . We find that the energies of valence band maximum and conduction band minimum are nearly linearly shifted with a biaxial strain in the range of −4% to 6%, and the band structure experiences a remarkable transition from semiconductor to metal with the appropriate compression (−5% strain). Under biaxial strain, the mobility of the electron and hole in monolayer GeP3 reduces and increases by more than one order of magnitude, respectively. It is suggested that it is possible to perform successive transitions from an n -type semiconductor (−4% strain) to a good performance p -semiconductor (+6% strain) by applying strain in monolayer GeP3, which is potentially useful for flexible electronics and nanosized mechanical sensors.